Analisis Implementasi Program Posyandu Keluarga di Lombok Timur - Sumbarwati, Nazaliya; Sastrawan, Sastrawan; Sismulyanto, Sismulyanto (Journal of Health Science and Prevention, 2025)
The Family Posyandu (PosGa) is a family-based health service innovation aimed at improving community health care access and quality, but faced significant challenges in rural areas. This study analyzed PosGa implementation in the Kalijaga Health Center area, East Lombok Regency, using a qualitative descriptive approach. Data were collected through 17 in-depth interviews, direct observation, and documentation. Findings revealed key challenges, including inadequate human resources, limited infrastructure, insufficient cadre training, and inconsistent incentives. Low participation from adolescents and the elderly, along with weak cross-sector coordination, further hindered effectiveness. Enhancing infrastructure, cadre capacity, and coordination, with a focus on inclusivity for all age groups, could strengthen PosGa as a comprehensive community health service.